The factors towards the awareness of halal logistics in WP Labuan - Muhamad , Mahathir; Mat Yunoh, Muhammad Naqib; Che Musa, Zul Karami; Yasoa', Mohd Rushdan; Mohd Sharif, Sharifa Najihah; Mohd Nor, Haslina (International Journal of Accounting, Finance and Business, 2025)
The purpose of this report is to investigate the barriers to Halal Logistics awareness. Logistics plays a key role in ensuring the halal cleanliness and sanitation of halal food by ensuring efficient transportation, storage, warehousing, and handling of halal food along the supply chain until it reaches the table. In actuality, halal logistics is a technique for preventing contamination of perishable commodities, raw materials, and food items throughout transportation and delivery. As a result, previous research literature reviews are employed to explain the above assumption in this conceptual piece. The data for this concept paper was gathered via theological research using a qualitative technique. The conclusions of this research may assist government authorities in identifying challenges, barriers, and strengths that should be emphasized when pressuring logistics companies in Malaysia to embrace halal standards. All public and private sectors should cooperate to address the problems, difficulties, and strengths of halal implementation in logistics services.